GAMBARAN PENERASI BAHAN TUMPAT KOMPOMER KE DALAM DENTIN GGI SULUNG DAN GIGI TETAP SETELAH PEMAKAIAN NON RINSE CONDITIONER (Evaluasi Scanning Electron Microscopy) - M. Fahlevi Rizal; Ismu Suharsono Suwelo; Hendrarlin Soenawan (Faculty of Dentistry, Universitas Indonesia, 2015)
The objective of this research was to know the difference of compomer (Dyract, Dentsply) penetration in dentin of primary and permanent teeth after applied by Non-Rinse Conditioner (NRS). The samples were observed by Scanning Electron Microscopy = SEM (1200x mag.) and the length of Compomer penetration in dentin tubules after applied by Non-Rise Conditioner were measured. T test showed that Compomer penetration in primary teeth was shorter compared to permanent teeth (t=3.474, p=0.001).